(untitled) (Research, Society and Development, 2020)
Objective: To identify the trend of Brazilian scientific production in theses and dissertations about nursing interventions aimed at the care of people with intestinal stoma for elimination. Methodology: This is a narrative review carried out in the catalog of theses and dissertations of the Coordination for the Improvement of Higher Education Personnel, with no time frame. Inclusion criteria: dissertations and theses from primary studies on the topic of interest and that converged with the objective of this review. The exclusion criteria were: dissertations and theses that addressed other types of stoma; review studies and those aimed at developing and validating an instrument for implementing nursing interventions. The analysis corpus was composed of seven studies, which were analyzed in full. Results: The target audience for the intervention actions were undergraduate nursing students, nursing professionals, families of people with colostomy for colorectal cancer and people with a stoma, with the most implemented modality of educational intervention. The strategies used were mediated by the use of the virtual learning environment, by the mobilization of actors to form local supporters, by the use of educational video and by telephone contact. It was possible to verify that all implemented interventions were valid and constructive as they made it possible to expand knowledge about intestinal stoma. Conclusion of the study: The production trend is related to the implementation of educational-type interventions, aimed at nursing professionals and academics.